Is trade liberalization of services the best strategy to achieve health-related Millennium Development Goals in Latin America? : a call for caution - San Sebastían, Miguel (2006)
Considers the main trade policy recommendations of the report of the Task Force on Trade, created for MDG 8, as a strategy to achieve the health-related MDGs in Latin America.